Consumer Acceptability of Fresh‐Market Muscadine Grapes. Issue 11 (14th October 2016) - Brown, Kelly; Sims, Charles; Odabasi, Asli; Bartoshuk, Linda; Conner, Patrick; Gray, Dennis
Abstract: The objective of this research was to investigate the acceptability of muscadine grape ( Vitis rotundifolia ) genotypes (cultivars and selections) and to correlate overall liking to other quality measurements to determine the main drivers of liking. Twenty‐two genotypes grown at the Univ. of Georgia–Tifton Campus were evaluated. Four retail commercial grape genotypes ( Vitis vinifera and "Concord") were also evaluated for comparison. Panelists familiar with muscadine grapes used the hedonic general labeled magnitude scale (HgLMS, –100 = strongest disliking of any kind ever experienced, +100 = strongest liking of any kind ever experienced) to rate overall liking and the liking of appearance, flavor, pulp texture, and skin texture. Puncture testing was done to assess grape berry texture, and compositional attributes soluble solids and pH were also measured. The sensory results indicated that the grapes were variable with overall liking scores from 12.2 to 39.6. The factors highly correlated with overall liking scores were muscadine flavor, pulp and skin liking, while a significant negative correlation was found between skin liking and skin texture and mechanical texture measures. The muscadine grapes with the highest overall liking scores were Ga. 5‐1‐34 and Ga. 2‐8‐21. Principal component analysis confirmed that grapes with a thinner skin and a higher pH tended to group around overall liking and flavor points. These results indicate that even among panelists familiar with muscadine grapes, skin thickness is a negative characteristic. Breeding for thinner skins may be a positive step in muscadines gaining a more widespread appeal in the fresh fruit market.